Hubungan Kecerdasan Emosional dan Motivasi Kerja dengan Kinerja Guru Taman Kanak-Kanak - Dina Ramanda; Riswanti Rini; Renti Oktaria (Jurnal PG-PAUD, 2020)
The purpose of this study is to find out the relationship between: 1) emotional intelligence and the performance of kindergarten teachers. 2) motivation of work with the performance of kindergarten teachers. 3) emotional intelligence and motivation of work with the performance of kindergarten teachers. This research uses the descriptive correlational method. The population was 82 kindergarten teachers in the Kecamatan Kedamaian. The research sample was 40 teachers with the purposive sampling technique. The data collection technique is a questionnaire. The data analysis technique is multiple linear regression. The results showed: 1) There is a relationship between emotional intelligence and the performance of kindergarten teachers, where thitung 3,217 ttabel 2,021, a significance of 0.04. 2) There is a relationship between work motivation and kindergarten teacher performance, where thitung 5.090 ttabel 2021, the significance is 0.01. 3) There is a relationship between emotional intelligence and work motivation together with the performance of kindergarten teachers, where Fhitung 3.526 3.23 Ftabel, 0.04 significance.Tujuan penelitian ini adalah mengetahui hubungan antara: 1) Kecerdasan emosional dengan kinerja guru TK. 2) Motivasi kerja dengan kinerja guru TK. 3) Kecerdasan emosional dan motivasi kerja dengan kinerja guru TK. Penelitian ini menggunakan metode deskriptif korelasional. Populasi sebanyak 82 guru TK Kecamatan Kedamaian. Sampel penelitian sebanyak 40 guru dengan teknik pengambilan sampel Purposive Sampling. Teknik pengumpulan data adalah angket. Teknik analisis datanya adalah regresi linier berganda. Hasil penelitian menunjukkan: 1) Terdapat hubungan antara kecerdasan emosional dengan kinerja guru TK, dimana t hitung 3,217 t tabel 2,021, sig 0,04. 2) Terdapat hubungan antara motivasi kerja dengan kinerja guru TK, dimana t hitung 5,090 t tabel 2021, sig 0,01. 3) Terdapat hubungan antara kecerdasan emosional dan motivasi kerja secara bersama-sama dengan kinerja guru TK, dimana Fhitung 3,526 3,23 Ftabel, sig 0,04. Kata Kunci: kecerdasan emosional, motivasi kerja, kinerja guru DOI: http://dx.doi.org/10.23960/jpa.v6n2.22255